Canadian Early-Childhood Educators' Perceptions of Children's Gendered Shy, Aggressive, and Prosocial Behaviors. Issue 3 (2nd July 2016) - Woods, Heather; Bosacki, Sandra; Coplan, Robert J.
ABSTRACT: Early childhood educators' (ECE) perceptions of gender roles may contribute to the development of children's own gender-role identities. This qualitative study examined 40 Canadian female ECEs' perceptions of gender and children's shy, aggressive, and prosocial behaviors. Content analysis of extensive interviews revealed three themes: (1) shyness as personality based, (2) influences on the behaviors, and (3) teachers' role in addressing gender and behavior. Most ECEs believed that shyness is a personality trait, exhibited equally among both genders, but displayed differently. In contrast, there were some inconsistencies as to which gender was perceived by the participants as more aggressive or prosocial. As well, findings suggested that participants believed that a teacher's role was to address behaviors within the classroom, and to help children express and understand their feelings through discussion and educational aids (e.g., books, videos, and community examples). Results are discussed in terms of educational implications and ECE training.